Bioethics and Burnout: Unpacking the Relationship - DeMichelis, Carey; Zlotnik Shaul, Randi; Kirsch, Roxanne (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
Canadian healthcare systems are facing unprecedented challenges in recruiting and retaining workers. Literature on healthcare burnout and professional exit suggest multiple intersecting causes. Understaffing, residual trauma, compassion fatigue, demanding hours, rigid hierarchies, and moral distress, interlock and compound to create and sustain the current burnout crisis. In the face of this frightening reality, healthcare institutions and governments are investing billions in wellness programs, aimed at attracting new workers and incentivizing staff retention. Amid this rapidly evolving landscape, our workshop asked: Does clinical ethics have a role in addressing the ongoing burnout crisis? If, as the research suggests, moral distress and moral injury are key drivers of the burnout problem, should bioethics be part of the “wellness” solution?